2000
DOI: 10.1039/b000080i
|View full text |Cite
|
Sign up to set email alerts
|

Sample preparation in the determination of phenolic compounds in fruits

Abstract: Introduction 2 Sample preparation 2.1 Hydrolysis 2.2 Fruit extracts 2.2.1 Juices and related products 2.2.2 Olive oil 2.2.3 By-products 2.3 Fruit 2.4 Peel and seed 2.5 Leaf 3 Quantification 4 Future needs-transfer to industry 5 Acknowledgements 6 References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
184
2
12

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(203 citation statements)
references
References 221 publications
5
184
2
12
Order By: Relevance
“…Compostos fenólicos totais de extratos de bagaço de uva* (g GAE.100 g -1 peso seco). Diversos autores concluíram que não é uma tarefa fácil encontrar um método único que seja adequado para a análise de um grupo diverso de fenólicos devido à diversidade das estruturas químicas e variação de sensibilidade dos compostos às condições de extração (ANTOLOVICH et al, 2000). Os teores de compostos fenólicos presentes no bagaço de uva representam uma grande variedade de compostos, incluindo os flavonóides.…”
Section: Compostos Fenólicos Totaisunclassified
“…Compostos fenólicos totais de extratos de bagaço de uva* (g GAE.100 g -1 peso seco). Diversos autores concluíram que não é uma tarefa fácil encontrar um método único que seja adequado para a análise de um grupo diverso de fenólicos devido à diversidade das estruturas químicas e variação de sensibilidade dos compostos às condições de extração (ANTOLOVICH et al, 2000). Os teores de compostos fenólicos presentes no bagaço de uva representam uma grande variedade de compostos, incluindo os flavonóides.…”
Section: Compostos Fenólicos Totaisunclassified
“…The lycopene concentration gradually increased on the storage for 42 days in both the varieties of tomatoes at both the temperature conditions. against oxidative stress from oxidizing agents and free radicals (Matkowski, 2006;Sarikurkcu et al, 2009;Antolovich et al, 2000).…”
Section: Issn: 2319-7706 Volume 6 Number 6 (2017) Pp 2997-3007mentioning
confidence: 99%
“…Tannat. Regarding the difference obtained from several studies, Antolovich (2000) concluded that it is not an easy task to find a single method that is suitable for the analysis of a group of various phenolic compounds due to the diversity of chemical structures and variation in sensitivity of the compounds to the extraction conditions (Antolovich et al, 2000) [13].…”
Section: Phenolic Compounds Contentmentioning
confidence: 99%